Circulating Micro-RNAs Predict the Risk of Recurrence in Triple-Negative Breast Cancer - Jouni Kujala; Maria Tengström; Sami Heikkinen; Mari Taipale; Veli-Matti Kosma; Jaana M. Hartikainen; Arto Mannermaa (Cells)
Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer with a high tendency for developing a recurrent disease. Circulating micro-RNAs (cmiRNAs) obtained through liquid biopsy are potential prognostic biomarkers for the assessment of TNBC recurrence risk. In this study, we sequenced cmiRNAs from the serum samples of 14 recurrent and 19 non-recurrent TNBC cases and compared expression profiles in relation to recurrence status, survival data and miRNA expression in matched tumor samples. Differential expression analysis between recurrent and non-recurrent cases identified ten differentially expressed (DE) cmiRNAs, of which cmiRNAs miR-21-5p (p = 0.030, HR = 1.87, 95% CI 1.06–3.30), miR-16-5p (p = 0.032, HR = 0.53, 95% CI 0.30–0.95), and miR-26b-5p (p = 0.023, HR = 0.52, 95% CI 0.29–0.91) were associated with recurrence-free survival in multivariable survival analysis. Expression profiles of matched tumor and serum samples were shown to correlate with each other. DE cmiRNAs were associated with common cancer-related signaling pathways and improved the overall predictive performance of the logistic regression model assessing the recurrence risk. Our results indicate that recurrent and non-recurrent TNBC differ in their cmiRNA expression profiles, and that three specific cmiRNAs can be used to assess the risk of recurrence in TNBC.